Shalat Tarawih Juziyyah: Komunitas Penghafal Al-Qur’an, Politik Identitas dan Otoritas Keagamaan Baru - Najiyya, Waffada Arief (JURNAL JAWI, 2020)
This article delves the reception of the Quran in Indonesia. This article, phenomenologically speaking, explores the tradition of tarawih juziyyah (the tarawih with completion of Quranic recitation) during Ramadan in Pondok Pesantren Madrasah Huffadz Krapyak Yogyakarta. This paper focuses on hierarchy of meanings emerging from the research subjects involved in the tradition. In addition to that, this research elaborates the transmission and transformation of the Quran taking place in ritual and non-ritual dimension of the tradition. Furthermore, it seeks out the hegemony and identity negotiation being hidden in the tarawih. Concluding the research, I argue that the tarawih juziyyah encapsulates two phenomena (prayer and khatm al-Qur’an) in one tradition and thus proves that the Quran holds sufficient power with which its memorizer gain, after sorts of politicization, highly prestigious status among muslims community.